Cyanogel auto-reduction induced synthesis of PdCo nanocubes on carbon nanobowls: a highly active electrocatalyst for ethanol electrooxidation. Issue 28 (9th July 2019) - Xu, Guang-Rui; Zhai, Ya-Nan; Li, Fu-min; Zhao, Guang-Tao; Li, Shu-Ni; Yao, Hong-Chang; Jiang, Jia-Xing; Chen, Yu
Abstract : Direct ethanol fuel cells (DEFCs) with a high conversion efficiency are quite promising candidates for energy conversion devices. Abstract : Direct ethanol fuel cells (DEFCs) with a high conversion efficiency are quite promising candidates for energy conversion devices. Herein, we have successfully synthesized PdCo alloy nanocubes supported on carbon nanobowl (denoted as Pd2 Co1 /CNB) nanohybrids by using the cyanogel auto-reduction method at high temperature. The morphology, composition and structure of Pd2 Co1 /CNB nanohybrids are characterized in detail, revealing that PdCo nanocubes have a high alloying degree and special {110} facets. In cyclic voltammetry measurements, Pd2 Co1 /CNB nanohybrids show a mass activity of 1089.0 A gPd −1 and a specific activity of 40.03 mA cm −2 for ethanol electrooxidation at peak potential, which are much higher than that of the commercial Pd/C electrocatalyst (278.2 A gPd −1 and 8.22 mA cm −2 ). Additionally, chronoamperometry measurements show that Pd2 Co1 /CNB nanohybrids have excellent durability for ethanol electrooxidation. A high alloying degree, special {110} facets and the CNB supporting material contribute to the high activity and durability of Pd2 Co1 /CNB nanohybrids, making them a highly promising Pt-alternative electrocatalyst for ethanol electrooxidation in DEFCs.